Quantitative Hepatitis B Surface Antigen as Biomarker for the Evaluation of Liver Fibrosis in Chronic Hepatitis B Patients (Iraqi Journal of Medical Sciences, 2024)
Background: The hepatitis B virus (HBV), are the primary causative agents of blood borne infectious disease. Cirrhosis and hepatocellular cancer are potential complications of chronic hepatitis. The quantitative HB surface antigen (qHBsAg) assessment can provide clinicians with more precise information. This can be especially useful for predicting treatment response, sustained virological response, disease progression, and other clinical situations, and laboratory-developed methods are not standardized. Persisting the HBV is caused by intrahepatic covalently closed circular DNA (cccDNA).Objective: To find out the relation between the degree of liver fibrosis and the levels of HBsAg and HBeAg and the usefulness of these two markers in prognosis of chronic hepatitis.Methods: Eighty-nine patients with chronic HBV infection took part in a cross-sectional study Gastrointestinal Tract Hospital in Medical City in Baghdad during a period from the first of September 2022 to the end of January 2023. Those patients were >18 years old with and without prior or current anti-HBV therapy and those patients were subjected to fibroscan to monitor liver fibrosis. qHBsAg and HBV (DNA) were taken from the medical records of those who recruited according to the specialist decision. Measuring the blood levels of HBsAg by using quantitative enzyme-linked immunosorbent assay (ELISA). Determining the HBeAG status by qualitative ELISA.Results: Fibroscan results showed that 47% had no fibrosis and the remaining 53% had different ranges of fibrosis, qHBsAg was directly correlated non significantly associated with DNA, age (P >0.05). Regarding HbeAg status (94.4% were negative, and 5.6% were positive). HBeAg was found to be associated with the staging of fibrosis (P
Keywords: Chronic HBV; Fibroscan; HBsAg; HBeAg